PENGARUH PENDAMPINGAN DETEKSI GERAK JANIN TERHADAP PARTISIPASI IBU DALAM SELF ASSESMENT GERAK JANIN - Seli Purnama Sari; Mardiani Mardiani; Asmawati Asmawati (Poltekkes Kemenkes Bengkulu, 2020)
Abstract: Stunted fetal growth (IUGR) shows poor fetal growth. Impaired fetal growth and fetal death are adverse effects of pregnancy, one of which is shown to decrease fetal movement. This study aims to determine the effect of maternal assistance in fetal motion detection on maternal participation in self-assessment of fetal motion at the Bengkulu City Fish Market health center. Quasi experimental research design with post test only with control group. With a sample of 40 people, 20 intervention groups and 20 control groups. The sample technique was consecutive sampling. The analysis used in the independent research ttest. The average maternal participation in self assessment after mentoring in the intervention group was 9.35 and the control group was 6.40. There is an effect of mentoring in calculating and assessing fetal movements through fetal motion cards on maternal participation in selfassessment of fetal motion (p value = 0,000 (p≤α = 0.05). It is expected that puskesmas and independent practice midwives continue to carry out fetal motion cards and can teach pregnant women how to calculate and fill the fetal motion card, as a prevention against fetal death.Keywords: Self Assesment, IUGR, IUFD